Improve penggantian transmisi rantai ke timing belt pada unit lipatan produk alat kesehatan dalam rangka peningkatan produktivitas di PT Aman Jaya - Alfian Ady Saputra; Yulia Widhianti; Maison Sormin (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
In the current era of globalization, competition is getting tougher, so companies must do something to survive and advance. PT Aman Jaya is a medical device company, where in the manufacture of medical devices, there is a sub process, namely the product folding process. In this process, problems occur that reduce running hours and cause productivity to decrease. The data used is from the company as well as field observations and analyzed to update the transmission of the product folding device, to reduce stoptime so that productivity increases. One of the causes of the problem is the transmission of the folding device, namely the chain. This transmission rusts due to lack of lubrication and if lubricated, the ash of the paper pulp sticks which over time becomes thick. So that the rotation is unstable, the chain jams, detaches from the sprocket, and breaks. After being analyzed and calculated according to the reference, the chain transmission was replaced with a timing belt of type L, number 165L, tooth are 44, length is 408.10 mm, and small pulley is 14, large pulley is 20, axle distance is 120 mm, for 1: 3 of motor ratio, 1500 rpm of rotation and 350 rpm of fold pulley rotation. By using a chain replacement timing belt, it is expected to reduce product folding trouble to increase productivity. The resulting update can reduce the folding problem, from an average stoptime of 74 min to 6 min. By reducing stoptime, folding problems can increase running hours and increase productivity by 40,800pcs.